Differentiation between Isomeric 4,5-Functionalized 1,2,3-Thiadiazoles and 1,2,3-Triazoles by ESI-HRMS and IR Ion Spectroscopy - Dmitrii M. Mazur; Elettra L. Piacentino; Giel Berden; Jos. Oomens; Victor Ryzhov; Vasiliy A. Bakulev; Albert T. Lebedev (Molecules, 2023)
A large variety of 1,2,3-thiadiazoles and 1,2,3-triazoles are used extensively in modern pure and applied organic chemistry as important structural blocks of numerous valuable products. Creation of new methods of synthesis of these isomeric compounds requires the development of reliable analytical tools to reveal the structural characteristics of these novel compounds, which are able to distinguish between isomers. Mass spectrometry (MS) is a clear choice for this task due to its selectivity, sensitivity, informational capacity, and reliability. Here, the application of electrospray ionization (ESI) with ion detection in positive and negative modes was demonstrated to be useful in structural studies. Additionally, interconversion of isomeric 4,5-functionalized 1,2,3-triazoles and 1,2,3-thiadiazoles was demonstrated. Application of accurate mass measurements and tandem mass spectrometry in MS2 and MS3 modes indicated the occurrence of gas-phase rearrangement of 1,2,3-triazoles into 1,2,3-thiadiazoles under (+)ESI-MS/MS conditions, independent of the nature of substituents, in line with the reaction in the condensed phase. Infrared multiple photon dissociation (IRMPD) spectroscopy enabled the establishment of structures of some of the most crucial common fragment ions, including [M+H-N2]+ and [M+H-N2-RSO2]+ species. The (−)ESI-MS/MS experiments were significantly more informative for the sulfonyl alkyl derivatives compared to the sulfonyl aryl ones. However, there was insufficient evidence to confirm the solution-phase transformation of 1,2,3-thiadiazoles into the corresponding 1,2,3-triazoles.